Morphological, water barrier and biodegradable properties of sugar palm nanocellulose/starch biopolymer composites incorporated with cinnamon essential oils - Syafiq, R. M. O.; Sapuan, S. M.; Mohd Zuhri, M. Y. M.; Othman, S. H.; Ilyas, R. A. (Walter de Gruyter, 2023)
In the past few decades, there has been increased interest in the use of natural fibers as reinforcement in bioplastic polymer composites because it is biodegradable. This is a result of the drawbacks of biodegradable polymer-based materials, which are brittle, intractable, and poorly water-sensitive. Natural fibers are chosen because they may be obtained organically, can be collected safely, and can be less expensive. In this work, cinnamon essential oil (CEO)/sugar palm nanocellulose/starch biopolymer composites were casted to investigate the morphological, water barrier and biodegradable properties. From the research, it shows water absorption increased regarding the plasticizer concentration. Besides, water vapor permeability (WVP) and solubility of the different concentration plasticizer used in the biopolymer shows an increasing trend due to high water content. All films degrade completely after the 12th day indicating the biodegradability of the film. Furthermore, seal strength for the lower concentrations of plasticizer shows the higher strength, while GS4.5 cannot be sealed due to high water contents. The images show the compatible films with slightly yellowish and transparent films. The variation of plasticizers did not affect the antibacterial activity of CEO inside the film forming solution. Overall, cinnamon essential oil (CEO)/sugar palm nanocellulose/starch biopolymer composites are good potential to enhance their suitability for food packaging applications.